ESTIMATING ATRIUM CONDITION BY MEANS OF HIGH RESOLUTION ECG AND ECHOCARDIOGRAPHY IN PATIENTS WITH PAROXYSMAL ATRIAL FLUTTER - G. I. Storozhakov; G. S. Vereshagina; N. V. Malysheva; E. A. Bugova (Российский кардиологический журнал, 2001)
Estimating atrium condition by means of high resolution ECG and echocardiography in patients with paroxysmal atrial flutter.